Evaluation of the Sensible Heat Storage Air Source Heat Pump for Residential Heating in Central-south China. (June 2016) - Jing, Zeng; Nianping, Li; Jianlin, Cheng; Yang, Zhang; Chen, Wang
Abstract: The operating performance and indoor thermal comfort of the sensible heat storage air source heat pump (ASHP) system were analyzed by detailed experiments and numerical calculation in this paper. The data field trial lasted for two months in Changsha, China. Specifically, the indoor temperature distributions in both the defrosting and no-frost outdoor conditions were investigated respectively through experiments. And the comparative analysis with the VRV system was conducted. Predicted mean vote (PMV) and predicted percent dissatisfied (PPD) were used to evaluate indoor thermal comfort. Experimental results and the calculated evaluation indexes depict that the sensible heat storage system can achieve improved indoor thermal comfort and lower energy consumption compared with the VRV system. The system is promising and suitable for residential heating in central-south China.